2022
DOI: 10.1177/10781552221092158
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to practice guidelines for the management of febrile neutropenia in patients undergoing hematopoietic stem cell transplantation: An observational study in a referral center in Iran

Abstract: Introduction Patients undergoing hematopoietic stem cell transplantation (HSCT) are suspected to develop febrile neutropenia (FN) and severe infections. Therefore, appropriate prescription of antibiotics in these patients is crucial to reduce the rates of morbidity, mortality, and antimicrobial resistance. The present study aimed to evaluate the physicians’ prescription and adherence to the FN clinical guidelines among patients undergoing HSCT. Methods This prospective observational single-center study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…[7][8][9] For example, a 2023 observational study found that antibiotic dosing and initial regimen recommendations were not followed in almost 60% of patients with febrile neutropenia who were undergoing hematopoietic stem cell transplantation. 10 T he American Cancer Society expects more than 2 million patients to receive a new cancer diagnosis in 2024. 1 The initial manifestations of malignancy, disease progression, and adverse reactions to treatment represent a significant disease burden, accounting for an estimated 4 million ED visits each year.…”
Section: Evaluation and Management Of Febrile Neutropenia In Patients...mentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] For example, a 2023 observational study found that antibiotic dosing and initial regimen recommendations were not followed in almost 60% of patients with febrile neutropenia who were undergoing hematopoietic stem cell transplantation. 10 T he American Cancer Society expects more than 2 million patients to receive a new cancer diagnosis in 2024. 1 The initial manifestations of malignancy, disease progression, and adverse reactions to treatment represent a significant disease burden, accounting for an estimated 4 million ED visits each year.…”
Section: Evaluation and Management Of Febrile Neutropenia In Patients...mentioning
confidence: 99%
“…Recent studies report poor adherence to guidelines for risk assessment and management of patients with febrile neutropenia and cancer 7-9. For example, a 2023 observational study found that antibiotic dosing and initial regimen recommendations were not followed in almost 60% of patients with febrile neutropenia who were undergoing hematopoietic stem cell transplantation 10. Another 2020 observational study found that guideline adherence was merely 0.4% in low-risk patients 11.…”
mentioning
confidence: 99%